Constraints and Improvement: A case Study of the Indonesia’s International Standard School in Improving its Capacity Building - Bambang Sumintono; Hamdan Said; Nora Mislan (Journal of Education and Learning (EduLearn), 2012)
Improving school capacity building becomes one of the major themes in the educational effectiveness research. This paper investigates implementation of the International Standard School (SBI) policy in Indonesia which as an effort of school capacity building improvement in the country. Using framework that is developed by King and Newman (2001), several dimensions of capacity building with relation to knowledge, skill and disposition of individual staff, and professional learning community in a secondary school that is located in a small city in West Java, Indonesia involved in the program is analysed. It is found that policy structure of Indonesia’s SBI has not been adequately designed and developed to gear the school towards significant direction in terms of improving its capacity building. Teachers have difficulties to reach ‘international requirements’ such as communicating in English in teaching, program to improve the language fluency also not worked properly. School was not utilizing capacity to increase professional learning community between teachers, but rely on usual program.